PENERAPAN BAHASA INDONESIA DALAM AKTA NOTARIS DI KOTA PONTIANAK - Samdera, Muhammad Reyza; Salem, Laurensius; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted on the need for the application of Indonesian language rules in legal language in each legal product issued by legal officials, especially notary products, namely notary deeds. Notary Deed is an official state document in its application, it is mandatories to use Indonesian language. The purpose of this study was to describe the use of spelling and diction deviations in notary deeds in Pontianak City. This research uses descriptive method with qualitative research forms. This research was conducted on two notary officials who issued a draft deed of establishment in the city of Pontianak, namely notary Basuki Raharjo, S.H. and notary Gina Inri Andriyani, S.H. Based on data analysis, there were 362 cases of language writing deviations, details of the deviation in the form of 235 cases of spelling irregularities (capital letters, italics, use of prepositions in and to, use of particles, combined form of words, use of word, and use of punctuation (point, comma, link, semicolon, colon, and parenthesis)) and 127 cases of dictation deviation (accuracy of diction and suitability of diction). Keywords: notary, notary deed, spelling, diction